Effect of Shakthi bandhasanas on Primary Dysmenorrhea - A Study Protocol of a Randomized Controlled Trial - Kanimozhi, Ramu; Gayathri, Annamalai; Kumaresan, Poornachandran; Sathiyanandham, Muniyappan; Jeevajothi, Chellapandiyan; Naveena, Arumugam; Radhika, Loganathan (Indian Journal of Integrative Medicine, 2024)
Primary dysme norrhea (PD) is recurrent lower abdominal pain that happens during the menstrual cycle and is not associated with any other pelvic pathology. In India prevalence of dysmenorrhea is 87.87% and incidence is 33.5% among adolescent girls. Yoga see ms to be effe ctive in regulating the various physiological functions. Shakthi bandasanas is a dynamic group of asanas which may have effect on abdominal region. Hence, we have planned this study to find the effect of shakthi bandasanas on primary dysmenorrhoea. A total of 80 subjects between 14 to 25 years will be recruited. This study adopted a randomized controlled trial. Study has 2 groups with 40 subjects in each group. Study group subjects will be recommended to practice shakthi bandasanas and control group will be rest in supine position for 21 days. Baseline and post intervention assessments will be done for all subjects. Outcome variab les are Menstrual symptom Questionnaire and Visual Analogue Scale. Data will be analysed using the Statistical Package for Social Sciences. Version 16. In this study, we will consider p (probability) value of 0.05 to be statistically significant. The result will be represented in bar diagram using the mean value of the dependent variables. If this study provides significant ch anges, then shakthi bandasanas may be adjuvant therapy in the management of primary dysmenorrhea. Ethical clearance was obtained (IEC IIYNMS/Approval/014/2023) and registered in a clinical trial (CTRI/2023/10/059308).